PROSPEK PEREKONOMIAN INDONESIA DALAM MEMASUKI AFTA - Basuki, Agus Tri (Jurnal Ekonomi & Studi Pembangunan, 2002)
This article will analyze Indonesia’s economic performance towards ASEAN free trade area (AFTA). From the economic performance, Indonesia is facing high threats, especially on the competitiveness of product and KKN (corruption, collusion, and nepotism) problem that cause high cost economy. So, government and businessman must anticipate it in order to strengthened Indonesia’s economy.